Formal and Substantive Compliance of Nazhir in the Use of Waqf Principal Funds for Operational Costs - Ahmad Wahyudi; Bagas Heradhyaksa; Pas Ingrid Pamesti; Zulkarnaen Ahmad (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
This study aims to evaluate the formal and substantive legal compliance of a Nazhir in using waqf principal funds for institutional operational expenses. It employs an empirical legal method with a socio-legal approach and a critical single-case study of Waqf Institution X in Jakarta. Primary data were obtained through a semi-structured interview with a Nazhir involved in fundraising, fund management, and institutional decision-making, while secondary data were derived from waqf regulations, Indonesian Waqf Board guidelines, fatwas, fiqh literature, scholarly publications, and publicly available institutional documents. The data were analysed qualitatively by comparing law in books with law in action through formal and substantive compliance frameworks. The findings indicate that the institution demonstrates elements of formal compliance through its reported registration, organizational structure, and productive waqf activities. However, the reported option to deduct operational expenses directly from the initial waqf contribution raises a substantive compliance problem because Nazhir remuneration should derive from management returns rather than be deducted from the designated principal. Contractual consent does not, by itself, legitimize such deductions because it remains subject to mandatory norms protecting waqf perpetuity. Limited written documentation and unclear separation between principal, returns, and operational expenses also create risks to legal certainty, transparency, and wakif protection. This study contributes a formal–substantive compliance framework for evaluating operational financing practices in contemporary waqf governance.